Implementing Website-Based School Information Systems in Public Elementary Schools Using Waterfall Model - Fauzan Asrin; Geby Vici Utami (Universitas Bina Darma, 2023)
This research focuses on implementing a web-based school information system at SDN 14 Pontianak City, a renowned public elementary school with a rich historical background. The study aims to address challenges related to ineffective internal information delivery within the school. Currently, reliance on group chats for school-related activities poses obstacles in efficiently disseminating crucial information, including new student registration, extracurricular activities, competition achievements, vision and mission statements, and important updates. To overcome these challenges, a website-based school information system is proposed. It aims to seamlessly deliver essential school-related information to a wider audience, including parents and prospective parents. The system ensures easy access to information that was previously confined to the school's internal environment. The research employs the structured development process of the waterfall model, utilizing context diagrams, data flow diagrams (DFD), and entity relation diagrams (ERD) for a well-defined system design. Rigorous testing using the black box approach ensures website functionality and reliability. Implementation of this web-based school information system is expected to substantially improve information dissemination, benefiting the entire school community by providing convenient access to vital information for parents and prospective parents. This improvement will foster enhanced communication and engagement within the school ecosystem.